One step apexification using two types of mineral trioxide aggregate - Moore, Abigail (Trinity College (Dublin, Ireland). School of Dental Science, 2008)
This research investigated the clinical and radiographic success of one step apexification of non-vital immature permanent incisors in children using 2 types of white MTA; white MTA Angelus and white MTA ProRoot®. The objective was to establish the effectiveness of white MTA as an apexification material for immature permanent incisors and propose one or both brands as a suitable and time efficient replacement to calcium hydroxide.
Keywords: Dental Surgery, D.Ch.Dent.; Ph.D. Trinity College Dublin